Intermediate uveitis as an initial presentation of HLA B27 associated spondyloarthropathy in an adolescent boy: A rare case report and review of literature - Panda, Prateek Kumar; Padhy, Srikant Kumar (Indian Journal of Child Health, 2019)
Juvenile ankylosing spondylitis is less prevalent in children, and usually, children are presented to the hospital with chronic inflammatory back pain, enthesitis, and often hip and shoulder joint involvement. A significant proportion of these children develop ocular complications such as anterior and intermediate uveitis. Most of these children have HLA B27 positivity. On the other hand, in cases with anterior and intermediate uveitis, a considerable proportion has positivity for HLA B27 antigen. Few of these patients, later on, develop other clinical features suggestive of ankylosing spondylitis. However, there are only a few anecdotal case reports of similar HLA B27 associated intermediate uveitis, who later on developed juvenile ankylosing spondylitis. The current case is a 12-year old boy, who initially had bilateral intermediate uveitis with HLA B27 positivity without any other systemic or musculoskeletal features. However, on follow-up he developed enthesis and sacroiliitis suggestive of ankylosing spondylitis. Both rheumatological and visual complains had an excellent clinical response to corticosteroids in this child. The current case report demonstrates the importance of evaluation for HLA B27 positivity in all children with isolated intermediate uveitis, even if systemic and musculoskeletal examinations are normal.